PENGARUH PHYSICAL EVIDENCE DAN VARIAN MENU TERHADAP LOYALITAS PELANGGAN WIZZMIE DI KOTA PASURUAN - Farikha, Fitra Ainun; Hastari, Sri; Subagio, Dyajeng Puteri Woro (Bhinneka Multidisiplin Journal, 2024)
This research aims to determine the influence of Physical Evidence and Menu Variants on Wizzmie Customer Loyalty in Pasuruan City. The sampling method uses Simple Random Sampling. Using the Slovin Formula, with a sample size of 94 respondents. The analysis used is research instrument testing in the form of validity and reliability tests, descriptive analysis, classical assumption tests, multiple linear regression analysis, hypothesis testing, and determinant coefficient tests. The research results show that the physical evidence variables and menu variants simultaneously have a significant effect on Wizzmie customer loyalty in Pasuruan City with a Fcount > Ftable value of 37.206 > 3.095. The physical evidence value partially has a positive and significant effect on Wizzmie customer loyalty in Pasuruan City with a tcount>ttable value of 6.878>1.661 and a sig value of 0.000>0.05. The menu variant value partially has a positive and significant effect on Wizzmie customer loyalty in Pasuruan City with a tcount>ttable value of 3.783>1.661 and a sig value of 0.000<0.05. The determinant coefficient (R2) obtained a value of 0.450, which shows that physical evidence and variance menu can influence customer loyalty by 45.0%. Meanwhile, other variables outside the scope of the research were 55.0%